Creative Problem Solving as a Catalyst for Transformative Learning - Kevin Dixon Gecowets; Weixin He; Sumi Lee (Adult Education Research Conference, 2024)
Creative Problem Solving (CPS) and Transformative Learning (TL) consider how dilemmas prompt new ways of thinking. This study will examine Transformative Learning outcomes of CPS-centered creative education.
Keywords: creative problem solving; transformative learning; creative education